(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Aim: The aim of the study is to observe the result of thyroidectomy without keeping drain tube. Methods: This is a prospective study of a series of patients who underwent thyroidectomy without drain from January 2017 to December 2019. Presence of any post-operative complications like hematoma, seromas and hemorrhage were recorded. Results: Among 105 patients included in this study only one patient had post-operative hematoma. There was neither hemorrhage nor seroma in other any patients. Proper hemostasis was maintained during surgery of all these cases. Their post-operative recovery was good. Conclusion: Drainage is may not be required after thyroidectomy if proper and adequate hemostasis is ensured. Bangladesh J Otorhinolaryngol; April 2020; 26(1): 41-44